Atrial and Ventricular Rate Response and Patterns of Heart Rate Acceleration during Maternal–Fetal Terbutaline Treatment of Fetal Complete Heart Block - Cuneo, Bettina F. (2007)
Terbutaline is used to treat fetal bradycardia in the setting of complete heart block (CHB); however, little is known of its effects on atrial and ventricular beat rates or patterns of heart rate (HR) acceleration. Fetal atrial and ventricular beat rates were compared before and after transplacental terbutaline treatment (10 to 30 mg/day) by fetal echocardiography in 17 fetuses with CHB caused by immune-mediated damage to a normal conduction system (isoimmune, n = 8) or a congenitally malformed conduction system associated with left atrial isomerism (LAI, n = 9). While receiving terbutaline, 9 of the 17 fetuses underwent fetal magnetocardiography (fMCG) to assess maternal HR and rhythm, patterns of fetal HR acceleration, and correlation between fetal atrial and ventricular accelerations (i.e., AV correlation). Maternal HR and fetal atrial and ventricular beat rates increased with terbutaline. However, terbutaline's effects were greater on the atrial pacemaker(s) in fetuses with isoimmune CHB and greater on the ventricular pacemaker(s) in those with LAI-associated CHB. Patterns of fetal HR acceleration also differed between isoimmune and LAI CHB. Finally, despite increasing HR, terbutaline did not restore the normal coordinated response between atrial and ventricular accelerations in isoimmune or LAI CHB. In conclusion, the pathophysiologic heterogeneity of CHB is reflected in the differing effect of terbutaline on the atrial and ventricular pacemaker(s) and varying patterns of HR acceleration. However, regardless of the cause of CHB, terbutaline augments HR but not AV correlation, suggesting that its effects are determined by the conduction system defect rather than the autonomic control of the developing heart.